Neutralizing Aptamers from Whole-Cell SELEX Inhibit the RET Receptor Tyrosine Kinase - Cerchia, Laura (Public Library of Science, 2005)
Targeting large transmembrane molecules, including receptor tyrosine kinases, is a major pharmacological challenge. Specific oligonucleotide ligands (aptamers) can be generated for a variety of targets through the iterative evolution of a random pool of sequences (SELEX). Nuclease-resistant aptamers that recognize the human receptor tyrosine kinase RET were obtained using RET-expressing cells as targets in a modified SELEX procedure. Remarkably, one of these aptamers blocked RET-dependent intracellular signaling pathways by interfering with receptor dimerization when the latter was induced by the physiological ligand or by an activating mutation. This strategy is generally applicable to transmembrane receptors and opens the way to targeting other members of this class of proteins that are of major biomedical importance.